Overshoot-tolerant primary frequency control of battery energy storage system for battery aging mitigation - Gu, Tingyun; Wang, Yu; Liu, Yiheng; Feng, Qihui; Peng, Qiao (Frontiers in Electronics, 2025)
Battery energy storage systems (BESSs) are required to provide frequency support to the grid in some cases, which increases the charge-discharge cycles of battery and accelerates its aging, especially in primary frequency control (PFC). However, the conventional PFC of BESS mainly focuses on the frequency support performance without adequately considering battery health. This paper proposes an adaptive PFC of BESS for battery aging mitigation, which adopts a novel overshoot-tolerant principle to recover the state of energy (SOE) of battery. Once the frequency support demand aligns with the SOE recovery demand, the BESS responds to the frequency deviation in a reverse way. Then, the battery can be charged or discharged more vigorously, and the SOE of battery can be adequately maintained at an ideal level. A multi-objective online optimization model is proposed to update the optimal PFC coefficient, which is solved by the non-dominated sorting genetic algorithm (NSGA-II). The simulation results verify the proposed method, which can effectively recover the SOE of battery with an improved frequency support performance. Moreover, the case study results also validate that the aging of battery can be mitigated by recovering the SOE.